CC-4066 therapy delivered to kidneys during cold storage and assessed with normothermic reperfusion is feasible and safe - Meertens, Pommelien; Mellati, Azita; Dumbill, Richard; Lo Faro, M. Letizia; Rozenberg, Kaithlyn; Mulvey, John; Fliri, Hans; Ploeg, Rutger; Hunter, James (Frontiers in Transplantation, 2023)
Introduction: Currently there is an urgent need to translate interventions that may be beneficial to marginal donor kidneys prior to transplant, to improve their quality from bench to bedside. This project investigated the effects of CC-4066, a potent dual inhibitor of cyclophilin proteins A and D, treatment during static cold storage (SCS) in a porcine model of renal ischemia-reperfusion injury (IRI) using Normothermic Reperfusion (NR). Materials and methods: Porcine kidneys and autologous blood were retrieved in pairs from a local abattoir (n=7). One kidney from each pair was randomly allocated to treatment and one allocated to control and flushed with preservation solution containing CC-4066 or vehicle. After 7 hours of SCS kidneys underwent 3h Normothermic Reperfusion (NR) with autologous whole blood while perfusion characteristics and samples were collected. Results: Perfusion and metabolic parameters showed similar trends and no statistical differences were observed between the groups. IL-6 showed a significant increase over time but no significant difference between groups (p-value 0.009 and 0.14 respectively, two-way ANOVA). Oxygen consumption and lactate levels were similar between groups but there was increased vacuolation on histology in the control group. Conclusions: The addition of CC-4066 during SCS of kidneys is safe and feasible and has no adverse or detrimental effects on perfusion during assessment on NR. There was no difference in cytokine levels although there was a trend towards less vacuolation on histology in the treatment group